The Polymer Effect on Nonlinear Processes in Decaying Homogeneous Isotropic Turbulence. (17th February 2013) - Cai, Wei-Hua; Li, Feng-Chen; Zhang, Hong-Na; Wang, Yue; Wang, Lu
Abstract : In order to study the polymer effect on the behavior of nonlinearities in decaying homogeneous isotropic turbulence (DHIT), direct numerical simulations were carried out for DHIT with and without polymers. We investigate the nonlinear processes, such as enstrophy production, strain production, polymer effect, the curvature of vortex line, and many others. The analysis results show that the nonlinear processes like enstrophy production (and many others) are strongly depressed in regions dominated by enstrophy as compared to those dominated by strain either in the Newtonian fluid case or in polymer solution case. Polymers only decrease the values of these parameters in the strongest enstrophy and strain regions. In addition, polymer additive has a negative effect on enstrophy and strain production, that is, depression of nonlinearity in DHIT with polymers.